PENERAPAN INKUIRI UNTUK MENINGKATKAN KEMANDIRIAN DAN HASIL BELAJAR SISWA KELAS X PEMASARAN 3 SMK NEGERI 3 SURAKARTA - -, Virginia Ika Dani Nurgiyantari -; -, Sri Wahyuni -; -, Salman Alfarisy Totalia - (Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
This research is aimed to improve self-directed and students? learning result in the subject bussiness planning trought implementation of inquiry learning in X Marketing 3 at SMK Negeri 3 Surakarta 2017/2018 academic year. The techniques of collecting the data used in the research are observation, interview, documentation and test. The technique of analyzing the data used are descriptive supported by quantitative and qualitative data. The procedures of this research are planning, acting, observing and reflecting.           The result of the research by implementing of Inquiry Learning is that it can improve the self-directed and students? learning result seen by the aspects of cognitive, affective and pshychomotor. The result of self-directed in the pre-cycle was 13,9% improved in the 1st cycle up to 75% and in the 2nd cycle up to 88,9%. The result of the students? learning result in cognitive aspect of the 1st cycle was 74,3% and improved in the 2nd cycle up to 77,8%. The result of students? learning result in affective aspect of 1st cycle was 83,3% and improved in the 2nd cycle up to 86,1%. The result of the students? result in pshychomotor aspect of the 1st cycle was 88,9% and improved in the 2nd cycle up to 97,2%.            Based on the result of this research, it can be concluded that the implementation of Inquiry learning can improve self-directed and students? learning result in the subject of Business Planning of X Marketing 3 class of SMK Negeri 3 Surakarta 2017/2018 academic year.